Pengembangan Activity Pembelajaran Ekoliterasi untuk Mengenalkan Literasi Budaya Khas Sukoharjo pada Anak Usia 5-6 Tahun - Prehatiningsih, Arip; Sufiati, Vivi; Edmawati, Mahmuddah Dewi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to develop eco-literacy-based learning activities to enhance the cultural literacy of local Sukoharjo traditions in children aged 5–6 years. The research used a Research and Development (R&D) method with the 4D development model (Define, Design, Develop, Disseminate). Expert validation results indicated that the product was feasible for use, and limited trials showed that the developed activities effectively increased children's active participation and understanding of local cultural and environmental values. This eco-literacy and culture-based learning model is not only contextually relevant but also contributes to holistic character development in early childhood. The resulting product has the potential to be replicated in other regions by adapting to local cultural values. Thus, this model offers an innovative alternative in early childhood education